Pengaruh Inovasi Produk, Inovasi layanan Dan Kualitas Layanan Terhadap Loyalitas Pelanggan PT.Pegadaian Melalui Kepuasan Sebagai Variabel Interven Di Masa Pandemi Covid-19 "Studi Kasus PT. Pegadaian Pasar Senen" - Akbar Indra Jaya, (2021)
This research was conducted to determine the effect of product innovation, service innovation and service quality on customer loyalty at the pawnshop branch of the Senen market, satisfaction as an intervention variable. Using the sampling method, namely non-probability sampling and purposive sampling. Source of data by distributing questionnaires to 100 respondents. The analytical tool used is SmartPLS 3.3. The following results obtained (1) Product innovation has a positive and significant effect on customer satisfaction with a path coefficient value of 0.366; (2) Service innovation has a positive and significant effect on customer satisfaction with a path coefficient value of 0.285; (3) Service quality has a positive and significant effect on customer satisfaction with a path coefficient value of 0.240; (4) Customer satisfaction has a positive and significant effect on customer loyalty with a path coefficient value of 0.439. It is concluded that product innovation, service innovation, service quality have an effect significant to customer satisfaction. And customer satisfaction has a significant effect on customer loyalty.